2021
DOI: 10.1093/rheumatology/keab539
|View full text |Cite
|
Sign up to set email alerts
|

Improving outcomes for patients hospitalized with gout: a systematic review

Abstract: Objectives Hospital admissions for gout flares have increased dramatically in recent years, despite widely available, effective medications for the treatment and prevention of flares. We conducted a systematic review to evaluate the effectiveness and implementation of interventions in patients hospitalised for gout flares. Methods A search was conducted in MEDLINE, Embase and the Cochrane library, from database inception to 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The intervention was developed with extensive stakeholder input, following a systematic literature review [ 15 ], audit and process mapping of gout care at our hospital [ 16 ]. The management pathway was designed as a quick-reference guide on optimal gout care for use by frontline clinicians and rheumatologists.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intervention was developed with extensive stakeholder input, following a systematic literature review [ 15 ], audit and process mapping of gout care at our hospital [ 16 ]. The management pathway was designed as a quick-reference guide on optimal gout care for use by frontline clinicians and rheumatologists.…”
Section: Methodsmentioning
confidence: 99%
“…For avoidable gout admissions to be prevented, strategies are needed to optimize care and increase uptake of treat-to-target ULT in hospitalized patients. A recent systematic review found a paucity of high-quality studies in people hospitalized for gout [ 15 ]. Specifically, no prospective studies to date had evaluated strategies designed to encourage ULT uptake and prevent re-admissions in hospitalized patients [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospitalizations due to gout also doubled in the United States, Canada and Sweden, contrasting large decreases in admissions for rheumatoid arthritis [5][6][7]. Despite this, few studies have investigated strategies to prevent avoidable gout admissions [8].…”
Section: Introductionmentioning
confidence: 99%